Effect of Using Demonstration Instruction Approach on the Performance of Mathematics Students in Public Secondary Schools in Rwanda: A Case of Karongi District (International Journal of Scientific Research and Management (IJSRM), 2024)
The aim of this paper was to determine the effect of Effect of using demonstration instruction approach on the performance of mathematics students in public secondary schools in Rwanda: A case of Karongi District’.The study used descriptive research design. Stratified sampling was used to determine a sample of 6 schools among other public secondary schools in Bwishyura sector in Karongi District. The head teachers of the sampled schools were purposively selected to participate in the study. Simple random sampling technique was further applied to obtain Mathematics teachers and students of senior 4,5 and 6, making 783 target students. The study used a sample of 230 respondents from the sampled schools. The collected data was analyzed using descriptive statistics, correlation, and regression analysis through the statistical package for social science (SPSS) version 21.The data collected were analyzed using multiple linear regression analysis. The result of the regression analysis indicates that demonstration Method, discussion method, cooperative learning method and problem solving have a positive effect on Performance of Mathematics students in public secondary Schools in Karongi District and the relationship is statistically significant (p=>0.05) and the relationship is in line with a priori expectation. Results showed significant positive relationship between demonstration instruction method and the performance of Mathematics students (r = .669, p = .0000). Multiple linear regression analysis showed that all demonstration instruction method contributed to 73% of variation on the performance, hence plays a vital role in performance of Mathematics students in public secondary schools in Karongi District. This study recommended that Mathematics teachers should use the demonstration instruction approach teaching Mathematics since it improves academic achievement.